Chemical shift assignments for Rv0577, a putative glyoxylase associated with virulence from Mycobacterium tuberculosis - Buchko, Garry W. (2011)
Approximately one-third of mankind has been exposed to Mycobacterium tuberculosis, the etiological agent responsible for tuberculosis (TB). As part of an effort to develop a new generation of anti-TB agents, the chemical shifts for the 261-residue, virulence-associated protein Rv0577 from M. tuberculosis has been extensively assigned.